Analysis of Marketing and Operational Planning in a Container Villa Rental Company - Ahembang Ahembang; Tanti Yanuar Rahmad; Rhian Indradewa; Muhammad Dhafi Iskandar (Syntax Corporation Indonesia, 2023)
In the tourism and housing industry, the container villa rental business is gaining popularity as a unique and innovative residential alternative. This business offers a different stay experience by providing comfortable and stylish container villas. The purpose of this research is to analyze marketing and operational planning in the container villa rental company PT Nahe Unggul Lestari. This research uses a qualitative approach with a case study as its research method. Data will be collected through interviews with company managers and related staff, as well as direct observation of operational processes and marketing promotions. The data that has been collected will be analyzed qualitatively using a thematic approach. The results show that marketing and operational planning in the villa container rental company has been carried out in a systematic and structured manner. This marketing and operational planning team is responsible for ensuring that the company has effective marketing and operational strategies to achieve its goals. The marketing and operational planning process at the villa container rental company is carried out by taking into account factors such as company needs, market needs, and the company's ability to pay.